Households Headed By Women and Physical Growth of Schoolchildren in Tláhuac, D.F. (Mexico) - Florencia Peña Saint Martin; Sergio López Alonso (Social Medicine Publication Group, 2024)
The present work is part of a research program examining the role of the family as mediator between basic human vital functions and social macro-processes. In order to evaluate conditions affecting physical development we examined the age-normed weight and stature of 410 primary school children who were enrolled in public primary schools of the Tláhuac delegation (one of the 16 political delegations in Mexico City). All schoolchildren had received a merit scholarship for their academic performance and were from poor families. Standardization of height and weight was done using the norms of the U.S. National Center for Health Statistics. 110 of these schoolchildren (68 girls and 42 boys) lived in households led by women. Among the 48 children with growth problems 15 (31%) were from female-led households. This finding indicates that this group of students has grown up in environments that have negatively affected their growth. Among growth delayed children households headed by women were over-represented at a rate almost double that of the general population. This data from schoolchildren with scholarships from the Tláhuac program demonstrates clearly the feminization of poverty and the structural vulnerability these women who single-handedly maintain households in conditions of poverty. At least among our subjects, we can conclude that households headed by women suffer a greater degree of poverty, that this poverty is passed on between generations and that it has a negative impact on children's wellbeing (as documented through growth parameters).